Serum N-Glycome Diversity in Teleost and Chondrostrean Fishes - Aoki, Kazuhiro; Kumagai, Tadahiro; Ranzinger, René; Bergmann, Carl; Camus, Alvin; Tiemeyer, Michael (Frontiers in Molecular Biosciences, 2021)
Recent advances in carbohydrate chemistry, chemical biology, and mass spectrometric techniques have opened the door to rapid progress in uncovering the function and diversity of glycan structures associated with human health and disease. These strategies can be equally well applied to advance non-human health care research. To date, the glycomes of only a handful of non-human, non-domesticated vertebrates have been analyzed in depth due to the logistic complications associated with obtaining or handling wild-caught or farm-raised specimens. In contrast, the last two decades have seen advances in proteomics, glycoproteomics, and glycomics that have significantly advanced efforts to identify human serum/plasma biomarkers for various diseases. In this study, we investigated N-glycan structural diversity in serum harvested from five cultured fish species. This biofluid is a useful starting point for glycomic analysis because it is rich in glycoproteins, can be acquired in a sustainable fashion, and its contents reflect dynamic physiologic changes in the organism. Sera acquired from two chondrostrean fish species, the Atlantic sturgeon and shortnose sturgeon, and three teleost fish species, the Atlantic salmon, Arctic char, and channel catfish, were delipidated by organic extraction and the resulting protein-rich preparations sequentially treated with trypsin and PNGaseF to generate released N-glycans for structural analysis. Released N-glycans were analyzed as their native or permethylated forms by nanospray ionization mass spectrometry in negative or positive mode. While the basic biosynthetic pathway that initiates the production of glycoprotein glycan core structures is well-conserved across the teleost fish species examined in this study, species-specific structural differences were detected across the five organisms in terms of their monosaccharide composition, sialylation pattern, fucosylation, and degree of O-acetylation. Our methods and results provide a platform for developing a fish N-glycome library that can establish a species-normative baseline for assessing N-glycosylation dynamics associated with pathogen invasion, environmental stress, and fish immunologic responses.